Complex Biophysical and Computational Analyses of GQuadruplex Ligands: The Porphyrin Stacks Back - Satta, Giuseppe; Trajkovski, Marko; Cantara, Alessio; Mura, Monica; Meloni, Claudia; Olla, Giulia; Dobrovolná, Michaela; Pisano, Luisa; Gaspa, Silvia; Salis, Andrea; De Luca, Lidia; Mocci, Francesca; et al. (Wiley-VCH, 2024)
G-quadruplexes (G4 s), as non-canonical DNA structures, attracta great deal of research interest in the molecular biology as wellas in the material science fields. The use of small molecules asligands for G-quadruplexes has emerged as a tool to regulategene expression and telomeres maintenance. Meso-tetrakis-(N-methyl-4-pyridyl) porphyrin (TMPyP4) was shown as one of thefirst ligands for G-quadruplexes and it is still widely used. Wereport an investigation comprising molecular docking anddynamics, synthesis and multiple spectroscopic and spectro-metric determinations on simple cationic porphyrins and theirinteraction with different DNA sequences. This study enabledthe synthesis of tetracationic porphyrin derivatives that ex-hibited binding and stabilizing capacity against G-quadruplexstructures; the detailed characterization has shown that thepresence of amide groups at the periphery improves selectivityfor parallel G4 s binding over other structures. Taking intoaccount the ease of synthesis, 5,10,15,20-tetrakis-(1-acetamido-4-pyridyl) porphyrin bromide could be considered a betteralternative to TMPyP4 in studies involving G4 binding.

G-quadruplexes (G4 s), as non-canonical DNA structures, attracta great deal of research interest in the molecular biology as wellas in the material science fields. The use of small molecules asligands for G-quadruplexes has emerged as a tool to regulategene expression and telomeres maintenance. Meso-tetrakis-(N-methyl-4-pyridyl) porphyrin (TMPyP4) was shown as one of thefirst ligands for G-quadruplexes and it is still widely used. Wereport an investigation comprising molecular docking anddynamics, synthesis and multiple spectroscopic and spectro-metric determinations on simple cationic porphyrins and theirinteraction with different DNA sequences. This study enabledthe synthesis of tetracationic porphyrin derivatives that ex-hibited binding and stabilizing capacity against G-quadruplexstructures; the detailed characterization has shown that thepresence of amide groups at the periphery improves selectivityfor parallel G4 s binding over other structures. Taking intoaccount the ease of synthesis, 5,10,15,20-tetrakis-(1-acetamido-4-pyridyl) porphyrin bromide could be considered a betteralternative to TMPyP4 in studies involving G4 binding.
Complex Biophysical and Computational Analyses of GQuadruplex Ligands: The Porphyrin Stacks Back
Keywords: DNA; G-quadruplexes; Molecular dynamics; Molecular recognition; NMR; DNA; G-quadruplexes; Molecular dynamics; Molecular recognition; NMR